A new species of Maytenus (Celastraceae) from the Brazilian Atlantic Forest, with evidence of molecular phylogeny, and two new synonyms for Maytenus floribunda - Biral, Leonardo; Smidt, Eric De Camargo; Bolson, Mônica; Lombardi, Julio Antônio (Phytotaxa, 2015)
A new species of Maytenus has been discovered in the Brazilian Atlantic Forest. The new taxon, Maytenus nemorosa, occurs mostly in ombrophilous rain forests at an elevation of 500 m to 1200 m. Maytenus nemorosa resembles M. gonoclada but differs from it by possessing oblong-elliptical leaves with entire margins and larger fruits with thicker pericarp walls. A phylogenetic analysis was conducted with nrITS and plastid matK regions, including the new species and additional taxa available from the NCBI-GenBank. The results from the phylogenetic analysis places Maytenus nemorosa nested within a clade of species that have fruits possessing a coriaceous pericarp and close to both Maytenus gonoclada and Maytenus salicifolia, as expected from morphological similarities. Additionally, M. cardenasii and M. erythrocarpa, from Bolivia, are both recognized as new synonyms for M. floribunda after an examination of their descriptions, types, and diverse collections.